Pengaruh Kualitas Cahaya Dan Frekuensi Aplikasi Paclobutrazol Terhadap Pertumbuhan Dan Hasil Tanaman Krisan (Chrysanthemum morifolium) - Dwi Ratno; Wiwin Dyah Ully Parwati; Yohana Theresia Maria Astuti; Ryan Firman Syah ryan (Journal of Sustainable Research In Management of Agroindustry (SURIMI), 2024)
Abstract - This study was to determine the effect of light quality and frequency of paclobutrazol application on the growth and yield of chrysanthemum plants. The research was conducted from February to April 2023 using factorial design and arranged in Split Plot Design consisting of Main Plot and Sub Plot. Main Plot was the effect of light quality using three different light colors, namely white light, red light, and blue light. Sub Plot was the frequency of paclobutrazol application which consists of 4 kinds, namely 0 times, 1 time, 2 times, and 3 times. Data analysis used in this study was analysis of variance with 5% confidence level. The results showed an interaction between the quality of light and the frequency of paclobutrazol application on the parameters of stem diameter and leaf area. Light quality had a good effect on the parameters of plant height, flower color, flower quality, number of flowers, number of leaves and flower diameter. The frequency of paclobutrazol application had a good effect on the parameters of plant height, flower color, flower quality, number of flowers, number of leaves and flower diameter. The best plant height was 106.39 cm, the highest number of leaves was 15.5, the best leaf area was 89.42 cm2, the best stem diameter was 0.41 inches, the best flower color with a score of 2.5, the best flower quality with a score of 2.8, the largest flower diameter was 7.93 cm, and the largest number of flowers was 5 flowers. Keywords: Light quality, Paclobutrazol, Chrysanthemum, Lamps